2016
DOI: 10.1016/j.apcatb.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Ni-, Pt- and (Ni/Pt)-doped TiO2 nanophotocatalysts: A smart approach for sustainable degradation of Rhodamine B dye

Abstract: Ni-, Pt-and (Ni/Pt)-doped TiO2 nanophotocatalysts: A smart approach for sustainable degradation of Rhodamine B dye, Applied Catalysis B, Environmental http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Photochemistry is a highly promising approach as it uses solar light (it must be noted that solar light consists of ~5% UV, ~43% visible, and ~52 % infra-red) as a renewable, abundant, and clean energy source [14][15][16]. In this sense, semiconducting materials, such as ZnO, TiO2, V2O5, and Nb2O5, have been recently proposed as efficient photocatalysts for the photodegradation of persistent organic pollutants [17][18][19]. Among these photocatalysts, ZnO is one of the most fascinating semiconductors as a result of its chemical stability, low toxicity, piezoelectricity, light conversion efficiency, antibacterial and antifungal activity, and high activity with regard to the production of reactive oxygen species (ROS) under UV light [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Photochemistry is a highly promising approach as it uses solar light (it must be noted that solar light consists of ~5% UV, ~43% visible, and ~52 % infra-red) as a renewable, abundant, and clean energy source [14][15][16]. In this sense, semiconducting materials, such as ZnO, TiO2, V2O5, and Nb2O5, have been recently proposed as efficient photocatalysts for the photodegradation of persistent organic pollutants [17][18][19]. Among these photocatalysts, ZnO is one of the most fascinating semiconductors as a result of its chemical stability, low toxicity, piezoelectricity, light conversion efficiency, antibacterial and antifungal activity, and high activity with regard to the production of reactive oxygen species (ROS) under UV light [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the Pt/SrTiO 3 nanoparticles for the photocatalytic oxidation of cyclohexane was investigated using the 1.5 wt% Pt/SrTiO 3 nanoparticles and the results showed that 1.5 wt% Pt/SrTiO 3 nanoparticles had a high photocatalytic stability after being used for five successive times, which is a common practice to verify the Pt/SrTiO 3 nanoparticles stability. 35 Accordingly, the enhancement of the catalytic activity of the doped Pt/SrTiO 3 photocatalyst compared to the prepared SrTiO 3 photocatalyst could be due to many reasons. First, the prevention of the recombination of the electron-hole pair by Pt atoms in the Pt/SrTiO 3 photocatalyst, as the doped metal atoms often act as electron traps, 36 second; the decrease of band gap energy that allows absorption of photons in the visible region, and finally the promotion of the interfacial electron transfer process as the Pt nanoparticles lead to formation of Schottky barriers on the SrTiO 3 , and work as electron traps, which facilitate the electron-hole separation.…”
Section: Photocatalytic Oxidation Of Cyclohexanementioning
confidence: 99%
“…ZnO has been frequently considered as an alternative to TiO 2 for photo-catalytic applications, since it shows similar activity in certain conditions [164] . In general, higher photo-catalytic reaction rates were obtained with ZnO samples than with TiO 2 Degussa P25, in spite of the low surface area of the ZnO samples.…”
Section: The New Promising Semiconductors In Photo-degradation Of Dyesmentioning
confidence: 99%
“…The increase in activity in these coupled systems is ascribed to charge separation at the interface, as it has been described for other semiconductor couples [167] . Similar to TiO 2 , another limitation of ZnO is its wide band gap (3.2 eV), which restricts light absorption to the UV region [164] . A possible strategy to extend ZnO absorption to visible light may be the modification of its valence band position by anionic doping, as has been achieved for TiO 2 [168] .…”
Section: The New Promising Semiconductors In Photo-degradation Of Dyesmentioning
confidence: 99%